Teachers' strategies in teaching listening comprehension at MAN 2 Kota Malang - Masruroh, Lailatul; Mubarok, Harir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The aim of this research is to find out the strategies used by teachers in teaching listening comprehension at MAN 2 Kota Malang. The objective of the research is to find out how the teachers implemented the strategy in teaching listening comprehension. Qualitative descriptive approach was used in the research. The research was conducted at MAN 2 Kota Malang and the participants were two English teachers of MAN 2 Kota Malang. The result of the research showed that the strategies used by teachers are Bottom-Up, Top-Down, and Socio-Affective strategy. Then, in the implementation of those strategies, the teacher used stages in teaching listening. The sequence was pre-listening, while-listening, and post-listening. In every single stage, the teachers conducted an activity in every stage with several media such as song, movie, and short dialogue.